(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
This research work aimed to compare if there are differences in the average of the scores obtained in the Pisa 2018 tests for the different countries evaluated in America in mathematics. A multiple comparison between independent means was made, from the statistical analysis of the data applying the ANOVA test, the statistical package SPSS v. 25. It was observed that there is evidence to reject the alternative hypothesis, therefore, the means are different. It was evidenced that Canada is the only country that is above the average of the set of OECD countries (489) in America with 512 points, ranking at level 3 on the mathematics scale, of 482 and 544 points. The United States with 478 points, Uruguay with 418, and Chile with 417 points, were located at level 2 of the mathematics scale, of 420 and 481 points, now, Mexico with 409 points, Costa Rica with 402 points, Peru with 400 points, Colombia 391 points, Brazil 389 points, and Argentina with 379 points, were located at level 2 of the mathematics scale, of 358 and 419 points. And very worrying is the case of Panama with 353 points, and the Dominican Republic with 325 points that do not reach any level on the mathematics scale.